Advocating legal safeguards for educators: Enhancing regulatory understanding - Hartati, Hartati; Helmi, Helmi; Putra, Firmansyah; Subekti, Dimas; Putra, Dinda Syufradian; Lestari, Amanda Dea (Community Empowerment, 2025)
This community service program aims to enhance understanding of legal protection for teachers in performing their professional duties. The implementation method includes preparation, problem identification, socialization, and monitoring and evaluation (Monev). Through this initiative, teachers gained comprehensive insights into their professional rights, obligations, and legal protection mechanisms as regulated by Law No. 14 of 2005 and Government Regulation No. 74 of 2008. The results showed a significant increase in participants' regulatory understanding, rising from 42% to 89%. The findings reveal that the primary obstacle to teacher protection is not a lack of regulation, but rather weak implementation and insufficient inter-institutional synergy. Consequently, systematic collaboration among local governments, education offices, professional organizations, and legal institutions is required, including the establishment of a Teacher Protection Task Force to ensure an effective and sustainable protection system.